P72 Maturation of sildenafil clearance in prematurely born infants with BPD associated pulmonary hypertension. Issue 6 (17th May 2019) - Nikrawesh, H; Engbers, AGJ; Völler, S; Simons, SHP; Koch, BCP; Knibbe, CAJ; Reiss, IKM; Flint, RB
Abstract : Background: Sildenafil is used as an off-label treatment for bronchopulmonary dysplasia (BPD) associated pulmonary hypertension in prematurely born infants. As there is only limited information on the pharmacokinetics (PK) of sildenafil in this population, the aim of this study is to investigate the PK of sildenafil in prematurely born infants with BPD associated pulmonary hypertension. Method: In this multicentre study, a population PK model for sildenafil in prematurely born infants was developed based on samples obtained using opportunistic sampling during clinical use of sildenafil. Data of seven subjects (42 plasma samples) were analysed by nonlinear mixed-effect modelling (NONMEM®7.3). Median (range) gestational age (GA) was 26.1 (24.1–27.6) weeks, current bodyweight 1960 (632–3157) grams, birthweight 635 (465–1125) grams and postnatal age (PNA) at start of therapy 64.9 (10.9–89) days. The median (range) treatment duration was 4.9 (1.6–13.1) weeks, with six subjects receiving oral doses of median 2.6 mg/kg/day (1.5–5.3) in three doses and one subject receiving oral and intravenous doses of 6.7 mg/kg/day in two doses. Results: The plasma concentration time profiles of sildenafil were best described by a one compartment model. Clearance (CL) and volume of distribution (Vd) for a child with a PNA of 64.9 days and bodyweight of 1.96 kg was 4.42 L/h ((RSE) 11%) and 29.5 L (32%), respectively. PNA was found to significantly influence CL, resulting in an increase of 10.7% in a week, and 43% in a month for a 65-day old infant. No other covariates (i.e. bodyweight, birthweight, GA, postmenstrual age and sex) were identified for CL or Vd. Conclusion: In this PK study, we characterised the pharmacokinetics of sildenafil in prematurely born infants and found that clearance increases with PNA. Due to the limited sample size in this study, further research in a larger population is needed to extend these findings. Disclosure(s): Nothing to disclose